Perhitungan laju korosi dan perancangan sistem proteksi katodik anoda korban di lambung kapal tugboat Bontang o4 PT Badak NGL Bontang - Saputra, R.A.; Setyawan, P.D.; Sugiman, S.; Zainuri, A. (Dinamika Teknik Mesin, 2017)
Corrosion happens differently for each point of hull plate which caused of corrosion rate differences. So that is very important to measure it for each point, which is calculated using Weight Gain Loss Method. The measurement of plate thickness that used is Ultrasonic Test Method conducted by PT BKI. To determine the condition of ship protection, then the coating and sacrificial anode system is evaluated by testing the composition and current and voltage of anode as well. Furthermore, the number and position of anode is also analyzed. So that the re-design of cathode protection is needed by referring to the PT BKI’s standards. Then the prediction of corrosion rate is calculated by using the design of cathode protection. The largest corrosion rates are in the amidships and portside for each plate lane, they are on the keel plate point K3 is 0.37 mm/years, pedestal plate point A4 is 1.05 mm/years, bilge plate point B4 is 0.62 mm/years and side plate point C5 is 0.39 mm/years. But the number of installed anode is 31 anodes with an irregular position. So in this study, done the redesign system of cathode protection based on regulations issued by PT BKI, with the result of the number of the anode is 56 units. Using the design, then carried a prediction by the result is lower, that on the keel plate is 0.073 mm/years, pedestal plate is 0.021 mm/years, bilge plate is 0.013 mm/years and the side plate is 0.014 mm/years.